2003
DOI: 10.1046/j.1523-1747.2003.12371.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Adipose Differentiation Related Protein and Neutral Lipid Droplet Accumulation in Keratinocytes by Skin Irritants

Abstract: Keratinocytes play an important role in skin irritation. In an attempt to investigate mechanistic bases of human skin irritation response, we recently identified the upregulation by skin irritants of adipose differentiation related protein (ADRP) in reconstituted human epidermis. ADRP is a lipid-storage-droplet-associated protein, governing deposition and release of lipids from droplets. The purpose of this study was to characterize, in a human keratinocyte cell line (NCTC 2544), sodium-dodecyl-sulfate-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Although it has been shown that several pathological or pharmacological stimuli enhance ADRP expression, the precise molecular mechanism regulating the expression is not fully elucidated. In previous studies, we and others demonstrated that an inflammatory signal, such as PMA or LPS, stimulates ADRP expression in macrophages (14,23,62), hepatocytes (46), and keratinocytes (15). We identified the Ets/AP-1 composite element in the mouse ADRP promoter and proved that it mediates, in part, the action of PMA or LPS, which enhances ADRP expression in RAW264.7 cells (23,62).…”
Section: Discussionmentioning
confidence: 60%
“…Although it has been shown that several pathological or pharmacological stimuli enhance ADRP expression, the precise molecular mechanism regulating the expression is not fully elucidated. In previous studies, we and others demonstrated that an inflammatory signal, such as PMA or LPS, stimulates ADRP expression in macrophages (14,23,62), hepatocytes (46), and keratinocytes (15). We identified the Ets/AP-1 composite element in the mouse ADRP promoter and proved that it mediates, in part, the action of PMA or LPS, which enhances ADRP expression in RAW264.7 cells (23,62).…”
Section: Discussionmentioning
confidence: 60%
“…keratinocytes exposed to irritants (Corsini et al, 2003). Since studies by other investigators have shown that activation of PPAR-b/d stimulates adipocyte differentiation (Bastie et al, 2000), we assessed if treatment of keratinocytes with PPAR-b/d activator was inducing an adipocyte phenotype in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…ADRP is associated with intracellular lipid droplets (Brasaemle et al, 1997;Frolov et al, 2000;Corsini et al, 2003;Schmuth, 2003) and reportedly facilitates fatty acid binding and uptake in COS-7 cells (Gao et al, 2000), as well as the transfer of triacylglycerol from lipofibroblasts to surfactant producing epithelial cells in the lung (Schultz et al, 2002). FIAF was previously reported to be increased in liver and white adipose tissue during fasting but the function of this protein is unknown.…”
Section: Figurementioning
confidence: 99%
“…Adfp expression is induced during differentiation of adipocytes and other specialized cells such as keratinocytes and trophoblasts (1,55), upon lipid loading, or under pathological conditions in other tissues and cells (5,11,13,22,54,60,66). Adfp expression is upregulated in 1246 cells by long-chain but not short-chain FAs (17).…”
mentioning
confidence: 99%